National Affection: Céline Dion - Hurley, Erin (National Performance: Representing Quebec from Expo 67 to Celine Dion, 2011)
In National Performance, Erin Hurley examines the complex relationship between performance and national identity. How do theatrical performances represent the nation in which they were created? How is Quebecois performance used to define Quebec as a nation and to cultivate a sense of 'Quebec-ness' for audiences both within and outside the province? In exploring Expo 67, the critical response to Michel Tremblay's Les Belles Soeurs, Carbone 14's image-theatre, Marco Micone's writing practices, Cľine Dion's popular music, and feminist performance of the 1970s and 80s, Hurley reveals the ways in which certain performances come to be understood as 'national' while others are relegated to sub-national or outsider status. Each chapter focuses on a particular historical moment in Quebec's modern history and a genre of performance emblematic of the moment, and uses these to elaborate the nature of the national performances. Winner of the Northeast Modern Language Association's Book Prize, National Performance is sophisticated yet accessible, seeking to enlarge the parameters of what counts as 'Quebecois' performance, while providing a thorough introduction to changing discourses of nation-ness in Quebec

Lara Fabian. Toutes les femmes en elle - Patinier, Jérémy (Lulu Press, 2011)
Peu de chanteuses sont aussi multiples : auteur, compositeur, comédienne et bien sûr chanteuse, Lara Fabian est une artiste, au sens plein du terme : extrêmement sensible, vibrant pour son art, elle ne laisse pas de marbre ! Soit on l’aime, follement, comme les milliers de fans qui la suivent, soit on l'attaque, avec acharnement… Belgo-sicilienne de naissance et québécoise de cœur, elle est devenue en 25 ans de carrière (en 2011, soit plus de 12 millions de disques vendus) une star dans ses deux pays, puis en France et aussi en Russie et au Brésil… Retour sur un parcours en chansons, en portraits, tout en émotion, dans l’intimité de l’artiste et de son travail, de son entourage jusqu'à ses fans, mais aussi sur les zones d’ombre... Anecdotes, révélations.

Survivre aux naufrages - Thalie, Lynda (Éditions La Semaine, 2011)
Elle en a fait du chemin, la petite Lynda qui a débarqué au Québec après avoir quitté une Algérie à feu et à sang! De l'intégrisme religieux à la liberté d'être, nous découvrons le parcours de la jeune fille affranchie, la naissance de l'artiste, de la conférencière, de la femme et de la mère qu'elle est aujourd'hui.

Kanadisches Französisch im Unterricht - Lynda Lemay: Les maudits Français [Le français canadien en classe - Lynda Lemay : « Les maudits Français »] - Thiele, Sylvia (Varietäten im Französischunterricht. 1. Französische Fachdidaktiktagung [Les variétés dans l'enseignement du français. 1er colloque de didactique du français], 2011)